Pengaruh Pemberian Pupuk Power Grow Terhadap Pertumbuhan Dan Produksi Pada Tanaman Kacang Panjang (Vigna Sinensis L - Mokoginta, Agustinus; Pobela, Elva; Paputungan, Hardiana F.; Ramadhan, Agung (Universitas Veteran Bangun Nusantara, 2024)
The purpose of this study was to determine the effect of Power Grow fertilizer on growth and production of several varieties of long bean plants (Chinese vinesL ). The method used is a RAK (randomized block design). The data obtained were analyzed using analysis of variance, and if it had a significant effect then it was continued with a 5% BNT test. The results of this study indicate that power grow fertilizer has no effect on the growth of long bean plants but varieties have a very significant effect on long bean growth and have no effect on long bean production. Whereas in the combination of treatments between fertilizers and varieties showed a real effect but no interaction occurred in the treatments Keywords: Power grow fertilizer, Growth, Production of long beans